Expression of TRPM gene and piezo ion channels in human lung cancers - Polatoğlu, Suna; Balci, Akın Eraslan; Önalan, Ebru; Tektemur, Ahmet; Çakmak, Muharrem (Turkiye Klinikleri, 2019)
Objective: Ions channels are responsible for cell processes such as apoptosis, proliferation, differentiation and are controlled by transient receptor potential melastatin (TRPM) cation channels and calcium homeostasis. Activation of ion channels facilitates cancer cell development by blocking autophagic activity. Blockage increases the autophagic activity and prevents cancer cell development. In our study, we aimed to show whether there is an increase in the expression of TRPM 2, 4, 5, 7, 8 and Piezo 1, 2 ion channels in cancerous lung tissue and its effect on autophagic activity. Thus, these channels can be considered as a therapeutic target for increased autophagic activity. Material and Methods: Forty cancers and 10 normal lung tissues were taken into work. cDNAs obtained by total RNA isolation, spectrophotometric RNA measurement, complementary DNA synthesis, high-capacity cDNA reverse transcription were amplified by real timepolymerase chain reaction in the presence of sequence-specific primers. Glyceraldehyde 3-phosphate dehydrogenase, TRPM 2, 4, 5, 7, 8, Piezo1, 2 genes were identified. Results: Twentynine of the cancer patients were male, 8 were female. Eight of the control group were male, 2 were female. 15 of the cancer patients have epidermoid, 16 adeno, 3 large cell, 3 small cell carcinoma. According to the control group, TRPM5 mRNA increased was seen in adenocarcinoma, epidermoid, small cell cancer groups. In the epidermoid carcinoma and small cell carcinoma groups, increase in TRPM7 mRNA was determined. Piezo1 mRNA was found to be positive in 20% of adenocarcinomas, 15% of epidermoid carcinomas and only 1 of small cell cancers. Piezo2 mRNA was significantly increased in adenocarcinoma, epidermoid, and small cell lung cancer. Conclusion: The loss of autophagic activity in lung cancer is associated with TRPM and piezo ion channels. When these channels are taken as a therapeutic target, they will initiate an important process in lung cancer treatment. © 2019 by Türkiye Klinikleri.
İnsan akciğer kanserlerinde TRPM gen ve piezo ıyon kanallarının ekspresyonu
Keywords: Lung cancer; Piezo 1; Piezo 2; TRPM channels